EFEKTIVITAS PENERAPAN GOOD AGRICULTURAL PRACTICES BUDIDAYA TEMBAKAU TERHADAP PRODUKTIVITAS TEMBAKAU DI KECAMATAN TLOGOMULYO, KABUPATEN TEMANGGUNG - Ismawati, Aisah Dwi; Maharani, Artita Devi; Rahmaningtyas, Avivah (Fakultas Pertanian UST, 2025)
This research was conducted in Tlogomulyo District, Temanggung Regency by analyzing the effectiveness of the application of Good Agricultural Practices (GAP) of tobacco and analyzing the effect of the application of Good Agricultural Practices (GAP) on tobacco productivity. The research method used is quantitative method, the sampling technique is done randomly or using random sampling technique as many as 96 respondents of tobacco farmers who are then analyzed using simple linear regression. The results showed that the level of effectiveness of the application of Good Agriculture Practices (GAP) tobacco is in the category of quite effective with a total score of 46.205% and the application of Good Agriculture Practices (GAP) has a positive and significant effect on tobacco productivity in Tlogomulyo District, Temanggung Regency. From the data analysis, the effectiveness of the application of Good Agricultural Practices (GAP) has a positive and significant effect from several indicators ranging from the right time, the right price, the right quality, and the right place to affect tobacco productivity in Tlogomulyo District, Temanggung Regency. Based on the results of the study, it is expected that farmers and local governments pay more attention and apply Good Agriculture Practices (GAP) to the cultivation of tobacco plants so that tobacco productivity continues to increase.